mTOR-Inhibition and COVID-19 in Kidney Transplant Recipients: Focus on Pulmonary Fibrosis - Granata, Simona; Carratù, Pierluigi; Stallone, Giovanni; Zaza, Gianluigi (Frontiers in Pharmacology, 2021)
Kidney transplant recipients are at high risk of developing severe COVID-19 due to the coexistence of several transplant-related comorbidities (e.g., cardiovascular disease, diabetes) and chronic immunosuppression. As a consequence, a large part of SARS-CoV-2 infected patients have been managed with a reduction of immunosuppression. The mTOR-I, together with antimetabolites, have been often discontinued in order to minimize the risk of pulmonary toxicity and to antagonize pharmacological interaction with antiviral/anti-inflammatory drugs. However, at our opinion, this therapeutic strategy, although justified in kidney transplant recipients with severe COVID-19, should be carefully evaluated in asymptomatic/paucisymptomatic patients in order to avoid the onset of acute allograft rejections, to potentially exploit the mTOR-I antiviral properties, to reduce proliferation of conventional T lymphocytes (which could mitigate the cytokine storm) and to preserve Treg growth/activity which could reduce the progression to severe disease. In this review, we discuss the current literature regarding the therapeutic potential of mTOR-Is in kidney transplant recipients with COVID-19 with a focus on pulmonary fibrosis.